Electricity for air conditioning and refrigeration technicians - Mahoney, Edward F. (Prentice Hall, 2000)
For courses in Basic Electricity taught to students of heating, ventilating, and air conditioning (HVAC). In a blend of theory and practical applications, this text presents a comprehensive introduction to electricity that's tailored specifically for future HVAC technicians.